Towards a Diffractive Mimesis: Karen Barad’s and Isabelle Stengers’ Re-Turnings - Rybačiauskaitė, Karolina (Journal of Posthumanism, 2022)
This article seeks to further the discussion of mimesis in the current new materialist philosophies that are charged with doubts about the potential of mimetic practices, i.e., practices of reflection, and propose a more differential /diffractive notion of mimesis. It argues that the concept of mimesis and performative approaches to knowledge making can be compatible. The figures of mimesis appear in the conceptualizations of both reflective and diffractive practices, and if mimesis is considered rather as a diffractive operation, it could be seen as having a different efficacy and ethico-political function. Drawing on Karen Barad’s and Isabelle Stengers’ arguments, I start by showing why in the representationalist view of knowledge making, the tool of mimesis is dysfunctional—it is a way of separating and classifying copies of reality. Then, I introduce a diffractive notion of mimesis in line with the mimetic re-turn in posthuman studies. From the perspective of relational understanding of knowledge making supported in Barad’s and Stengers’ ethico-political proposals, mimesis can be perceived as a tool for provoking change and thus, imply a need to do it carefully.